Papel reproductivo y productivo de las mujeres esclavas en Costa Rica en el siglo XVIII - Acuña León, María de los Ángeles (2008)
This article is about the sexual and economic exploitation that female slaves faced in the province of Costa Rica during the eighteenth century. It studies their role as reproducers of slave labor reviewing the colonial legislation in this respect. It also analyzes their role as wealth producers examining the different economic functions that they fulfilled as labor force and merchandise. In addition it refers to the punishments, to the diseases suffered by these slave women, and to some of their strategies to survive the abuse and exploitation they faced